HUBUNGAN MOTIVASI BERPRESTASI DENGAN DISIPLIN KERJA GURU TK DI KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU - Sri Marlisa; Wusono Indarto; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Based on observations while in the field related to the achievement motivation and work discipline Kindergarten Teacher In New Simpang Village District of Pekanbaru City Handsome encountered symptoms such as: the majority of teachers do not perform their duties in a timely, Some teachers there who do not make the teaching, lack of vigor in the process teaching students, teachers do not care about the students who lack the spirit of learning, it can be seen from many of the students were playing around, sleep, and out of, noisier, and storytelling in the learning process but the teachers do not care about them, and less communicative teacher led to the impression of a teacher has closed personalities, this situation causes the distance between teacher and pupil. And based on the linearity test can be seen that the value of the significance of the Linearity of 0.000. Because of the significance of less than 0.05, it can be concluded that the variables of achievement motivation to discipline teachers working relationship exists erat.Dari simple correlation analysis (r) obtained correlation between achievement motivation and discipline teachers (r) is 0.696 with probability 0.000. therefore the probability of <0.05 (0.000 <0.05), then Ho is rejected This suggests that there is a strong relationship with the achievement motivation and work discipline. While the direction of the relationship is positive, meaning that the higher the higher the achievement motivation. discipline of teachers. The coefficient of determination is generated is equal to r2 = 0484, p = 0.000 (p <0.05), it can be seen that the influence of achievement motivation 48.4% of the labor discipline teachers.Key word: Achievement Motivation, Work Discipline Teachers